Intelligent transport systems standards - Williams, Bob, 1947- (Artech House ITS library., 2008)
This one-stop resource provides a state-of-the-art review of intelligent transport systems, services, and supporting technologies, and updates you on the latest ITS standards governing communications, technical support, information technology, and identification technology. You find details on standards covering everything from traveler information and traffic management, to weather monitoring and emergency response.